Mapping the Primary and Secondary Metabolomes of Carob (Ceratonia siliqua L.) Fruit and Its Postharvest Antioxidant Potential at Critical Stages of Ripening - Marios C. Kyriacou; Chrystalla Antoniou; Youssef Rouphael; Giulia Graziani; Angelos Kyratzis (MDPI AG, 2021)
Six critical stages corresponding to major morphophysiological events in carob fruit ripening were defined, and changes in the primary and secondary metabolome and in vitro antioxidant capacity were examined in two genotypes collected at low (15 m) and high (510 m) altitudes from genetically identified and georeferenced trees. Soluble carbohydrates were analyzed by HPLC-RI, macro-minerals by ion chromatography coupled to conductivity detection and polyphenols by UHPLC-Q-Orbitrap-HRMS. spectroscopy facilitated assays for condensed tannins and in vitro free-radical scavenging capacity of 1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric-reducing antioxidant power (FRAP). The fruit respiration rate and moisture content declined sharply during the transition from the breaker to green pedicel stage. Sugar accumulation spiked at the onset of fruit coloration and culminated at 498.7 ± 8.4 mg g−1 dry weight (dw) in the late ripe stage, while the ratio of reducing sugars to sucrose decreased from 3.45 ± 0.32 to 0.41 ± 0.02. The total phenolic compounds and condensed tannins declined with ripening, particularly during the transition from the breaker to green pedicel stage. Eighteen polyphenols were identified and quantitated, with catechins and hydrolyzable tannins being dominant until the onset of fruit coloration. The transition to the green pedicel stage signaled a precipitous decline (90.9%) in catechins, hydrolyzable tannins (60.2%) and flavonol glycosides (52.1%) concomitant to the rise in gallic acid, which was putatively fueled by the enzymatic hydrolysis of gallotannins in immature fruit. Catechins, hydrolyzable tannins and flavone glycosides were more abundant at higher altitudes and gallic acid at lower altitudes. An antioxidant capacity was also favored by higher elevations and declined with ripening, particularly after the breaker stage. Correlations with FRAP and DPPH assays were significant for the total phenolic content, condensed tannins, catechins and hydrolyzable tannins. The highest correlation factors were obtained for epigallocatechin-gallate (r = 0.920 and r = 0.900; p < 0.01). Although the sharp drop in hydrolyzable and nonhydrolyzable tannins and catechins compromised the in vitro antioxidant capacity at physiological maturity, it also reduced the astringency and configured a palatable organoleptic fruit profile. These changes unraveled significant episodes in the ripening-related secondary metabolism of the carob fruit. They further highlighted the value of immature carob as a potent source of gallotannins, with putative in vivo anti-inflammatory action, and of catechins beneficial in preventing and protecting against diseases caused by oxidative stress.